"I didn't want to be on Suboxone at first…" – Ambivalence in Perinatal Substance Use Treatment. Issue 4 (July 2019) - Ostrach, Bayla; Leiner, Catherine
Abstract : Objectives: The objectives of this article are to present findings from recent qualitative research with patients in a combined perinatal substance use treatment program in Central Appalachia, and to describe and analyze participants' ambivalence about medication-assisted treatment for opioid use disorder (OUD), in the context of widespread societal stigma and judgement. Methods: We conducted research in a comprehensive outpatient perinatal substance use treatment program housed in a larger obstetric practice serving a large rural, Central Appalachian region. The program serves patients across the spectrum of substance use disorders but specifically offers medication-assisted treatment to perinatal patients with OUD. We purposively and opportunistically sampled patients receiving prescriptions for buprenorphine or buprenorphine-naloxone dual product, along with prenatal care and other services. Through participant-observation and semi-structured interviews, we gathered qualitative data from 27 participants, in a total of 31 interviews. We analyzed transcripts of interviews and fieldnotes using modified Grounded Theory. Results: Participants in a combined perinatal substance use treatment program value supportive, non-judgmental care but report ambivalence about medication, within structural and institutional contexts of criminalized, stigmatized substance use and close scrutiny of their pregnancies. Women are keenly aware of the social and public consequences for themselves and their parenting, if they begin or continue medication treatment for OUD. Conclusions: Substance use treatment providers should consider the social consequences of medication treatment, as well as the clinical benefits, when presenting treatment options and recommendations to patients. Patient-centered care must include an understanding of larger social and structural contexts.